CONDITIONS FOR FORMING THE ABILITY OF PEDAGOGICAL STUDENTS TO USE MIND MAPS IN PEDAGOGICAL WORK - Lidia G. Shestakova; Marina V. Lapenok (Russian Journal of Education and Psychology)
Background. In conditions of a large information flow and accessibility of information, problems often arise related to the ability to process it, analyze it, and optimally memorize it. One of these tools is mind maps, which in this study were considered as didactic means of structuring, ordering, visualization, systematization, and establishing relationships.